Application of Sampling Strategies for Hot-Mix Asphalt Infrastructure: Quality Control-Quality Assurance Sampling; Specification for Performance Test Requirements - Tsai, Bor-Wen; Yu, Jiangmiao; Monismith, Carl L. (IntechOpen, 2011)
None